Kafaah Sebagai Pertimbangan Dalam Perkawinan Menurut Mazhab Syafi’i - Abu Bakar Khazali (Universitas Islam Sumatera Utara, 2018)
Abstract Kafaah concept as one of the considerations of marriage according to Syafi'i’s School is used as a luzum condition or a prerequisite for marriage. It means that the marriage of the unfaithful couple is still legal. Only if the guardian disagrees with the marriage, he or she has right to cancel the marriage. The appointment of Imam Shafi'i’s school is oriented to mutual benefit that is to avoid the disunity of the family and to avoid the appearance of disgrace due to unmarried marriage. Thus, it can be simplified to say that a woman may marry a non-perforated man as long as she agrees with this and so does her guardian. Or the guardian may marry a woman with a non-perforce as long as the woman is told about her future husband's condition clearly and she accepts it so the marriage is legal.Keywords: Kafaah, marriage